Entropy generation and heat transfer analysis of magnetic nanofluid flow inside a square cavity filled with carbon nanotubes - P. Sudarsana Reddy; P. Sreedevi; V. Nageswara Reddy (Chemical Thermodynamics and Thermal Analysis, 2022)
Combination of MWCNTsandwater based nanofluid flow, isentropic lines and isotherms features inside a square enclosure with radiation and magnetic field is examined numerically in the current article. The dimensionless equations representing entropy generation, heat and momentum are solved numerically by applying finite difference scheme. The changes in the sketches of isotherms, streamlines and isentropic fields with dissimilar values of radiation parameter (0.01≤R≤0.1), volume fraction of nanoparticle parameter (0.01≤ϕ≤0.1), Rayleigh number (103≤Ra≤104), Prandtl number (5.2≤Pr≤8.2) and magnetic parameter (0.1≤M≤0.7) have scrutinized and are plotted through sketches. The scatterings of rates of heat transfer with respect to these parameters are also depicted through graphs. Non – dimensional rates of heat transfer intensifies in the nanofluid region with augmenting values of radiation parameter. The sketches of temperature lines of water−−MWCNTs based nanofluid lost their nature in the central part of the chamber and they are virtually vertical shape close to the right cold wall as the values of volume fraction of carbon nanotubes rises. 7.2% augmentation in heat transfer rate is noticed when 4% volume fraction of MWCNTs are added to the base fluid .